Cardiac Resynchronization Therapy in Non-Ischemic Cardiomyopathy: Role of Multimodality Imaging - Stătescu, Cristian (Diagnostics (Basel), 2021)
Non-ischemic cardiomyopathy encompasses a heterogeneous group of diseases, with a generally unfavorable long-term prognosis. Cardiac resynchronization therapy (CRT) is a useful therapeutic option for patients with symptomatic heart failure, currently recommended by all available guidelines, with outstanding benefits, especially in non-ischemic dilated cardiomyopathy. Still, in spite of clear indications based on identifying a dyssynchronous pattern on the electrocardiogram (ECG,) a great proportion of patients are non-responders. The idea that multimodality cardiac imaging can play a role in refining the selection criteria and the implant technique and help with subsequent system optimization is promising. In this regard, predictors of CRT response, such as apical rocking and septal flash have been identified. Promising new data come from studies using cardiac magnetic resonance and nuclear imaging for showcasing myocardial dyssynchrony. Still, to date, no single imaging predictor has been included in the guidelines, probably due to lack of validation in large, multicenter cohorts. This review provides an up-to-date synthesis of the latest evidence of CRT use in non-ischemic cardiomyopathy and highlights the potential additional value of multimodality imaging for improving CRT response in this population. By incorporating all these findings into our clinical practice, we can aim toward obtaining a higher proportion of responders and improve the success rate of CRT.